2016
DOI: 10.1155/2016/1314709
|View full text |Cite
|
Sign up to set email alerts
|

Proangiogenic Features of Mesenchymal Stem Cells and Their Therapeutic Applications

Abstract: Mesenchymal stem cells (MSCs) have shown their therapeutic potency for treatment of cardiovascular diseases owing to their low immunogenicity, ease of isolation and expansion, and multipotency. As multipotent progenitors, MSCs have revealed their ability to differentiate into various cell types and could promote endogenous angiogenesis via microenvironmental modulation. Studies on cardiovascular diseases have demonstrated that transplanted MSCs could engraft at the injured sites and differentiate into cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
153
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 110 publications
(107 reference statements)
5
153
0
1
Order By: Relevance
“…Previous studies have revealed that the myxoma arises from a multipotential endocardial or subendocardial reserve mesenchymal cell which can differentiate into fibrocytes, myocytes, or endothelium [10]. To date, a number of putative markers for mesenchymal stem cells have been reported, including CD44 [11]. Our immunohistology data confirmed the expression of CD44 in myxoma.…”
Section: Resultssupporting
confidence: 82%
“…Previous studies have revealed that the myxoma arises from a multipotential endocardial or subendocardial reserve mesenchymal cell which can differentiate into fibrocytes, myocytes, or endothelium [10]. To date, a number of putative markers for mesenchymal stem cells have been reported, including CD44 [11]. Our immunohistology data confirmed the expression of CD44 in myxoma.…”
Section: Resultssupporting
confidence: 82%
“…Such perivascular localization has also been demonstrated for MSCs in several tissues through the body, which support the proposition that MSCs are fundamental to the healing of many tissues. MSCs in the bone marrow are ontogenically distinct populations taking over various biological functions, such as niches for HSCs (6, 12, 13), progenitor cells for bone formation during bone remodeling or repair (14), for cartilage and adipocyte formation, and vascular support (1517). …”
Section: Mesenchymal Stem Cells or Marrow Stromal Cellsmentioning
confidence: 99%
“…It has been theorized that hMSCs reduce cardiac fibrosis 15 and enhance angiogenesis 16 largely through paracrine signaling (PS) mechanisms. 17,18 Moreover, recent studies have demonstrated that hMSC PS can modulate cardiomyocyte ion channel/pump activity.…”
Section: Introductionmentioning
confidence: 99%